(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: In type 2 diabetes, Interleukin-6 (IL-6) facilitates atherosclerosis through the promotion of chronic inflammation and endothelial dysfunction. Increased IL-6 levels in insulin-resistant conditions exacerbate lipid irregularities and vascular inflammation, hastening plaque development. The inflammatory milieu elevates cardiovascular risk in type 2 diabetes individuals. To see the correlation betweenIL-6, Insulin resistance (HOMA-IR) and Atherogenic Index of Plasma (AIP) in type 2 Diabetes mellitus. Materials and methods: A hospital-based cross-sectional observational study was carried out in the Department of Biochemistry Chittagong Medical College, Department of Endocrinology of Chittagong Medical College Hospital and Chattogram Diabetic Hospital. One hundred (100) type 2 diabetes mellitus patient was included in the study by nonprobability consecutive sampling. Important variables in this study were serum IL-6, HOMA-IR and AIP (Atherogenic Index of Plasma). Results: Serum IL-6 concentration is significantly positively correlated with waist circumference, Atherogenic Index of Plasma, LDL/HDL ratio in type II diabetes mellitus. The IL6 value is positively correlated with AIP in type II Diabetes Mellitus patients having increased waist circumference. There is a significant association of Atherogenic Index of Plasma (AIP) by Interleukin-6 (IL-6) HOMA-IR (Homeosttaic Model Assessment-Insulin Resistance) waist circumference. Conclusion: Adipose tissue macrophage infiltration is a major inflammatory mechanism promoting insulin resistance and diabetes. Scavenger receptors on vessel wall macrophages recognise and internalise oxidatively changed lipids such oxidised LDL, forming foam cells. IL-6 secretion may vary by macrophage polarization in type 2 diabetes mellitus. JCMCTA 2025 ; 36 (2) : 2-6